Ocular Manifestation of Human Immunodeficiency Virus - Kapoor, Shivangi; Dhawan, Aeshvarya; Tomar, Vijay Pratap Singh (Asian Journal of Medical Research, 2023)
Background: HIV is a dreaded virus that significantly deteriorates the quality of life of affected individuals. The main source of HIV infection in India is involved in high-risk behaviours. Early recognition of ocular manifestations of HIV/AIDS is essential since these ocular manifestations may be the primary or only presentation. This has implications for the prognosis of the disease. Aim and objective: To document various ocular manifestations in HIV/AIDS cases. Subjects and Methods: objective: To document various ocular manifestations in HIV/AIDS cases. Material and methods: This was a hospital-based observational study done at a tertiary eye care centre in north India, over 5 years period (January 2017 to January 2022). Overall, 92 patients were enrolled for the study. Results: Out of 92 HIV patients, 69 (75%) were males and 23 (25%) were females. Maximum eyes had visual acuity ranging from 6/6-6/12. 74 patients (59 males and 15 females) had heterosexual exposure, and 11 patients (6 males, 4 females and 1 child) had blood transfusion as a risk factor. Out of 92 HIV patients 35 patients (38%) had ocular involvement. Maximum patients 13 (37%) with Cytomegalovirus (CMV) retinitis followed by 7 (20%) were of HIV retinopathy. The associated systemic disorders included 48 patients with pulmonary tuberculosis. Conclusion: Ophthalmologists need to be highly aware of various ocular and systemic spectrums of HIV. Increased emphasis on early diagnosis, treatment and regular ophthalmic examination in all HIV/AIDS patients is the rule.